Manajemen Kurikulum Pesantren Salaf Darul Falah “Amtsilati” Jepara - Mufassirul Alam; Fikri Maulana (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2021)
This study aims to describe the curriculum at the Darul Falah Islamic Boarding School